Pregled delovanja družinskih centrov v izbranih evropskih državah in okviri razvoja družinskih centrov v Sloveniji - Kuhar, Metka (Teorija in praksa, 2011)
The article firstly introduces the concept and basic characteristics of family centres as a public living room, a widespread community support practicefor families with preadolescent children in different European and non-European countries. The general introduction is followed by two good practice examples - German and Swedish. We then present the selected Slovenian organisations/programmes for parents and children and draw the conclusion that none of them approaches the idea of a family centre as providing self-initiated community support for families. The concluding part opens a discussion of both hindrances to the development of family centres in Slovenia and their societal-social potential
Keywords: Družina; Family; child; Children; Otroci; Parents; Starši; Local communities; Lokalne skupnosti; Slovenia; Slovenija; družinski centri